Reporting antimicrobial susceptibility and detection of carbapenemase production in single and double carbapenemase-producing Gram-negative clinical isolates: a nationwide proficiency study - Fernández-Cuenca, Felipe; Delgado-Valverde, Mercedes; Guridi-Fernández, Pablo; Gimeno-Cardona, Concepción; Hidalgo-Díaz, Carmen; Pascual, Álvaro (Frontiers in Microbiology, 2025)
PurposeThe objective was to assess the ability of Spanish clinical microbiology laboratories to report reliable carbapenem susceptibility test results and to detect carbapenemase production (CP) and/or carbapenemase genes in double (DCP) and single carbapenemase-producing (SCP) isolates.MethodsTwelve isolates (8 SCP and 4 DCP) selected from the Andalusian Reference Laboratory were sent to 83 laboratories with requests for MICs and phenotypic and genotypic tests used for CP.ResultsOverall, there was lower essential agreement and a higher number of clinical errors in DCP than in SCP isolates. Phenotypic tests showed higher sensitivity for DCP isolates than for SCP isolates: lateral flow immunoassay (99.0% vs. 95.1%), carbapenem inactivation method (100% vs. 93%) and chromogenic media (100% vs. 83.3%); conversely, sensitivities for DCP versus SCP isolates was lower using disk diffusion with inhibitors (83.3% vs. 90.4%) and hydrolysis-based assays (81.3% vs. 86.1%). Molecular methods showed higher sensitivity for DCP isolates than phenotypic methods, and higher sensitivity for DCP isolates than for SCP isolates. In addition, concordance between genes detected and the reference was higher in DCP than in SCP isolates (98.9% vs. 83%). However, blaVIM-1 and blaIMP-8 were not detected in 77.5% and 42.2% of the determinations, respectively, for DCP isolates.ConclusionThe main differences between DCP versus SCP isolates were the lower reliability of gradient strips, higher overall sensitivity of phenotypic methods for DCP isolates, but lower sensitivity with disk diffusion inhibitors and hydrolysis-based assays. Molecular assays were generally more sensitive for carbapenemase gene detection in DCP than in SCP isolates, although concordance was lower.